School of Law Annual Report 2018: Embracing change in an Evolving world - Singapore Management University (Institutional Knowledge at Singapore Management University, 2019)
The Annual Report highlights the School of Law’s modest achievements and developments over the past year, as well as the substantive impact of these initiatives.